An overview of efficiency and profitability in Islamic banking: a comparative study between Islamic banking and conventional banking / Maha Alandejani - Alandejani, Maha (Universiti Teknologi MARA, 2022)
Islamic banks are similar to conventional banks, but differ in some practices, financial contracts, and transactions. The functions and transactions of Islamic Banking and Finance (IBF) are based on Sharia principles, which involve risk sharing. Therefore, there is a significant difference in the applications of lending and investment between Islamic and conventional banks. This review paper aims to map IBF- measurement that related to efficiency and profitability issues, by presenting briefly the nature of IBF, including the prohibition of interest and gambling, with the definition of IBF instruments. It reviews the most valuable existing empirical literature that investigated the efficiency and profitability of Islamic banking, which shows that the business model and techniques for measuring performance in Islamic banking does not differ significantly from that of conventional banking. This paper also discusses the critical terms in the financial methods that are used in IBF studies. It is found that the objectives of profit maximisation and cost minimisation are not vital for IBF and the performance of Islamic banks should be evaluated with indication of the level of promoting socio-economic development. Our finding concludes that, the social objectives of Islamic banks can be achieved after adapting new structures, not only for Islamic banks, but also for central banks, and banking regulations